2001
DOI: 10.1021/bi002246m
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Active Site Residue Arginine 218 in Firefly Luciferase Bioluminescence

Abstract: Firefly luciferase catalyzes the highly efficient emission of yellow-green light from substrate firefly luciferin by a sequence of reactions that require Mg-ATP and molecular oxygen. We had previously developed a working model of the luciferase active site based on the X-ray structure of the enzyme without bound substrates. In our model, the side chain guanidinium group of Arg218 appears to be located in close proximity to the substrate's hydroxyl group at the bottom of the luciferin binding pocket. A similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
141
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(159 citation statements)
references
References 39 publications
17
141
1
Order By: Relevance
“…In order to test whether the mutant strains were specifically affected in translation termination or displayed a more general translational defect, we devised an in vivo misincorporation assay. Replacing arginine in position 218 of luciferase with serine inactivates the enzyme (6). To test whether luciferase-R218S was suited as a misincorporation reporter, two different versions were generated.…”
Section: Vol 24 2004 Role Of Rac and Ssb1/2p In Translational Fidelmentioning
confidence: 99%
“…In order to test whether the mutant strains were specifically affected in translation termination or displayed a more general translational defect, we devised an in vivo misincorporation assay. Replacing arginine in position 218 of luciferase with serine inactivates the enzyme (6). To test whether luciferase-R218S was suited as a misincorporation reporter, two different versions were generated.…”
Section: Vol 24 2004 Role Of Rac and Ssb1/2p In Translational Fidelmentioning
confidence: 99%
“…Click beetle luciferases, which produce different colours, have also been cloned (17,18). Mutagenesis studies identified the residues important for the bioluminescence activity and colours of these luciferases (19)(20)(21)(22)(23)(24). Three mechanisms have been proposed to explain bioluminescence colour modulation by beetle luciferases: (I) non-specific solvent and orientation polarizability effects (15,16); (II) specific active-site interactions with the emitter (25); and (III) the effect of the conformation of the active site on the rotational properties of the oxyluciferin thiazine rings (26).…”
mentioning
confidence: 99%
“…These models were further confirmed by the independent studies: the residual activity of the luciferase mutant, in which Lys529 was changed to Ala, was less than 0.1% (Branchini et al, 2000). The role of others residues of the luciferase active site was supported by mutagenesis methods (Branchini et al, 1999(Branchini et al, , 2000(Branchini et al, , 2001(Branchini et al, , 2003. Fig.…”
Section: Spatial Structure Of Firefly Luciferase and Its Complexes Wimentioning
confidence: 52%
“…The residue R220 (the residue R218 in P.pyralis luciferase) is highly conservative and necessary for the green emission of firefly luciferases. Its substitutions led to the red bioluminescence, 3-15-fold decrease in activity, extended luminescence decay times and dramatic increase in K m values (Branchini et al, 2001). The G216N/A217L double substitution in L. mingrelica luciferase caused the similar type of effects but of less extent.…”
Section: Rational Protein Design Approach To Produce the Stable And Amentioning
confidence: 95%